Management of Infantile Spasms During the COVID-19 Pandemic. (October 2020) - Grinspan, Zachary M.; Mytinger, John R.; Baumer, Fiona M.; Ciliberto, Michael A.; Cohen, Bruce H.; Dlugos, Dennis J.; Harini, Chellamani; Hussain, Shaun A.; Joshi, Sucheta M.; Keator, Cynthia G.; Knupp, Kelly G.; McGoldrick, Patricia E.; et al.
Circumstances of the COVID-19 pandemic have mandated a change to standard management of infantile spasms. On April 6, 2020, the Child Neurology Society issued an online statement of immediate recommendations to streamline diagnosis and treatment of infantile spasms with utilization of telemedicine, outpatient studies, and selection of first-line oral therapies as initial treatment. The rationale for the recommendations and specific guidance including follow-up assessment are provided in this manuscript. These recommendations are indicated as enduring if intended to outlast the pandemic, and limited if intended only for the pandemic health care crisis but may be applicable to future disruptions of health care delivery.